2002
DOI: 10.1108/02640470210454001
|View full text |Cite
|
Sign up to set email alerts
|

CUNY+ Web: usability study of the Web‐based GUI version of the bibliographic database of the City University of New York (CUNY)

Abstract: A previous article reported the usability evaluation of the information database called CUNY+ of the City University of New York (CUNY) in New York City, USA. This is a text‐based information system available on the wide‐area network in its various campuses for faculty, students and researchers. This present article describes the usability evaluation of this CUNY system’s Web and GUI version called the CUNY+ Web. A comparison of the results of both usability studies, and a description of the applicability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Oulanov and Pajarillo 24 Efficiency, helpfulness, and adaptability Brinck et al 25 Functionally correct, efficient to use, easy to learn and remember, error tolerant, and subjectively pleasing MIT Information Services and Technology Department 26 Navigation, language and content, functionality, architectural and visual clarity Lee 27 Usefulness, effectiveness, satisfaction, supportiveness, and intuitiveness Nielsen 28 Learnability, efficiency, memorability, low error rate or easy error recovery, and satisfaction Booth 29 Usefulness, effectiveness, learnability, and attitude Mayhew 22 and Smith and Mosier 23 Consistency, user control, appropriate presentation, and error handling Information coding, minimal actions, flexibility, orientation and help, spatial organization, consistency, recognition rather than recall, prompting, remove the extraneous, data set reduction (continued) measure the completion of tasks and difficulties while users interact with Cam Trees, Information Cube, and Information Landscape visualizations on different data sets by Wiss et al 55 The results showed that these visualizations behaved differently on different data sets, and a guideline was provided for the selection of visualization for a specific data set. Similarly, 11 operational tasks were identified by Wehrend and Lewis 45 that one might do with a visualization, including identify, locate, and distinguish.…”
Section: Authorsmentioning
confidence: 97%
“…Oulanov and Pajarillo 24 Efficiency, helpfulness, and adaptability Brinck et al 25 Functionally correct, efficient to use, easy to learn and remember, error tolerant, and subjectively pleasing MIT Information Services and Technology Department 26 Navigation, language and content, functionality, architectural and visual clarity Lee 27 Usefulness, effectiveness, satisfaction, supportiveness, and intuitiveness Nielsen 28 Learnability, efficiency, memorability, low error rate or easy error recovery, and satisfaction Booth 29 Usefulness, effectiveness, learnability, and attitude Mayhew 22 and Smith and Mosier 23 Consistency, user control, appropriate presentation, and error handling Information coding, minimal actions, flexibility, orientation and help, spatial organization, consistency, recognition rather than recall, prompting, remove the extraneous, data set reduction (continued) measure the completion of tasks and difficulties while users interact with Cam Trees, Information Cube, and Information Landscape visualizations on different data sets by Wiss et al 55 The results showed that these visualizations behaved differently on different data sets, and a guideline was provided for the selection of visualization for a specific data set. Similarly, 11 operational tasks were identified by Wehrend and Lewis 45 that one might do with a visualization, including identify, locate, and distinguish.…”
Section: Authorsmentioning
confidence: 97%
“…At the same time, some of these researchers have increased the dimensionality of "usability" by including one or more elements of evaluation in its conceptualisation. These included "learnability" and "likeability" (Blandford & Buchanan, 2002;Booth, 1989;Constantine & Lockwood, 1999;Hix & Hartson, 1993;Nielsen, 1993;Schneiderman, 1992;Swett, 2002), "utility" (Bernérus & Zhang, 2010;Brooke, 1991;Zaharias, 2009), "memorability" and "error" (Marta, 2011;Nielsen, 1993;Swett, 2002;Yordanova, 2007), "quality of use" (Bevan, 1995), "content usability" (Lamb, 1995), "outcomes", "process" and "task" (Thomas, 1998), "control" and adaptability" (Oulanov & Pajarillo, 2002), "accessibility", "trustfulness" and "universality" (Bernérus & Zhang, 2010;Caldwell et al, 2004;Dee & Allen, 2006;Yordanova, 2007), "reliability" (Constantine & Lockwood, 1999;Nielsen, 1995;Siritongthaworn, Krairit, Dimmitt & Paul, 2006) and "web usability" (Brophy & Craven, 2007). These studies are fundamentally grounded on the technical aspects of usability, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Interface effectiveness is one of the most important aspects of usability as it is the medium through which users communicate and interact with the system. Oulanov and Pajarillo [33] state that usability tool entails the following eight criteria: Affect, Adaptability, Control, Helpfulness, Efficiency, User Effort, Measures of Effectiveness, and Retrieval Features. Furtado et al [14] also consider usability from ease of use point of view and add that usability should also include ease of learning.…”
Section: Usabilitymentioning
confidence: 99%
“…Shackel [42] defined usability as "the artifact's capability, in human functional terms, to be used easily, effectively and satisfactorily by specific users, performing specific tasks, in specific environments". Nielsen [33] defines usability as "the measure of quality of experience of user while using the product". Usability is defined in ISO 9241-11 [22] as the "the extent to which a product can be used by specified users to achieve specified context of use".…”
Section: Introductionmentioning
confidence: 99%